167Epidemiology of food choking deaths in Japan: Time trends and regional variations. (2nd September 2021) - Taniguchi, Yuta; Iwagami, Masao; Sakata, Nobuo; Watanabe, Taeko; Abe, Kazuhiro; Tamiya, Nanako
Abstract: Background: We aimed to investigate the nationwide epidemiology of food choking deaths in Japan. Methods: Using Japan Vital Statistics death data (2006-2016), we identified food choking deaths based on the 10th revision of the International Statistical Classification of Diseases code W79 (Inhalation and ingestion of food causing obstruction of respiratory tract). The demographics of people with food choking deaths; temporal trend of food choking deaths by the year (overall and by age group) and the day of year; and prefecture variations, were reported. Results: 52, 366 people experienced food choking deaths (median age, 82 years, 53% were men, and 57% occurred at home). The highest number of food choking deaths occurred in January 1, 2, and 3, in that order; and lowest in June. Despite a constant total number of cases at around 4000 yearly, the incidence proportion declined from 16.2 to 12.1 per 100, 000 population from 2006 to 2016 among people aged 75-84 years. The proportion peaked at 53.5 (2008) and decreased to 43.6 (2016) among people aged ≥85 years. Prefecture variations occurred in the number of food choking deaths, highest in Niigata and lowest in Kyoto. Conclusions: The results suggest targets (by age group, region, and day of the year) for the prevention of food choking deaths. Time trends and regional variations may be related to the consumption of Japanese rice cake (mochi), known as a major cause of food suffocation in Japan. Key messages: The number of food choking deaths in Japan was highest on New Year's Day.